Gamifying the Museum: Teaching for Games Based 'Informal' Learning - Sanchez, Eric; Pierroux, Palmyre (European conference on games based learning, 2015)
In this paper we present a study of master students working with the concept of gamification (Deterding et al., 2011; Bonenfant & Genvo, 2014; Sanchez, 2014) to design an informal learning activity in a natural history museum. The teaching unit was a project-based course covering fundamental concepts related to the use of games for educational purposes, and is part of the Information Architecture program at ENS of Lyon. The winter 2015 semester included one week of project work at the Museum of Nature in Sion, Switzerland. We present the course organization and pedagogical approach for the teaching unit. Based on observations, recordings and documentation of the students' process and products, we analyze the core concepts that became relevant in the students' game design for this informal learning setting. Specifically, we identify the notion of 'games as metaphors of the subject to be learned' (simulation), and 'games as spaces for reflexivity,' where players are prompted to assess their modes of thinking and behaving (feedback). We also discuss the extent to which this project aligned with the museum director's objectives of integrating a game-based learning activity in the permanent exhibition, with its collection of material objects, unique physical spaces, and use of multimodal resources. The exhibition had the narrative aim of highlighting the concept of anthropocene. This is a rather complex theme dealing with environmental changes and humanity's influence on the emergence of a new geological epoch. We analyze the ways in which the students integrated perspectives on informal learning with principles of gamification to engage their target audience in understanding the concept of anthropocene: young people (12-15 years old) on school field trips. We conclude by discussing the implications of this study for teaching game based informal learning in higher education programs, and we reflect on potential tensions and values of integrating games in learning activities in museums that became apparent from this study.